Gashb and Itlaf Arrangements in KHES and Authority of Justice (Review of Chapter XV of Book II of KHES) - Sufiarina, Sufiarina; Sudrajat, Herman; Mahmud, Hamidullah (Brawijaya Law Journal, 2020)
As a guide for judges in the Religious Court, the Supreme Court has issued Perma No.2 of 2008 concerning the Compilation of Sharia Economic Law (KHES). It contained Gashb and Itlaf, in Book II about the Covenant, whereas Gashb and Itlaf have interpreted as deprivation and destruction. Briefly, Gashb and Itlaf seem to be an offence because of the phrase taking or destroying someone else's property. Offence in the field of Islamic economics is the absolute authority of the State Court. For this reason, it is necessary to examine whether Gashb and Itlaf included in the context of Islamic economics. It also needs to be examined whether Gashb and Itlaf are the absolute authority of the Religious Court. Normative juridical research carried out by discussing Book II of KHES, specifically Chapter XV. It then analysed with the absolute competence of the Religious court, the provisions of Article 49 of the Law of Religious Court. The analysis complemented by a study of legal principles in Islamic economics. Comparisons also made with the concepts of legal relations in the Civil Code, especially regarding the binding and offence in the Criminal Code.The research results of Gashb and Itlaf do not originate from the contract and do not include business activities with Islamic economic principles. Thus Gashb and Itlaf are not included in the absolute authority of the Religious Court. Gashb and Itlaf are not intended as offences because the sanctions are compensation claims. Claims are filed based on lawsuits that violate the law and become the absolute authority of the State Court. Placement of Gashb and Itlaf in KHES is wrong because it does not include Islamic economic activities, so it must have removed from KHES.